Symbolic forms and cultural studies : Ernst Cassirer's theory of culture - Hamlin, Cyrus; Krois, John Michael (Yale University Press, 2004)
Cassirer's conception of culture & theory of symbolism anticipated much of later cultural theory. The essays in this volume explore aspects of his thinking & demonstrate the influence that it had on later scholarship.